Village Teachers’ Value Orientations - Stančikaitė, Regina (Acta Paedagogica Vilnensia, 1997)
The present scientific article discusses the structure of value characteristics for village teachers from various agricultural schools and third-year students of the Lithuanian Agricultural Academy, who chose the specialization of vocational teacher. Both groups of subjects appeared to prefer such traditional terminal values as good health and a happy family life, whereas needs of self-actualization were less significant. The analysis of the hierarchy of instrumental values revealed the significance of self-actualization needs in both groups of respondents. These results may reflect the social passiveness of the subjects and their need to attain more conformist goals. Regardless of this the investigation of instrumental values showed that country-based teachers tend to be more socially active and prefer values of self-actualization. The analysis of the hierarchy of values showed that the education system needs to pay more attention to the stimulation of self-actualization values in order to meet the demands of today’s social and economic situation.